Analysis of the Presence of Anopheles Larvae in the City Areas in DKI Jakarta on the Risk of Indigenous Malaria Cases in 2022 - Sinthania Karunia Magdalena; Mursid Rahardjo; Sulistiyani (Utan Kayu Publishing, 2023)
Malaria is one of the diseases that until now is still a special concern for tropical countries such as Indonesia. Prevention of non-indigenous malaria transmission has recently become a priority for the Indonesian government's program to minimize the incidence. This study aims to analyze the presence of anopheles larvae in city areas in DKI Jakarta province which have the potential to be at risk of causing the emergence of indigenous malaria cases in 2022 by observational survey methods and strengthened by literature studies. The results were obtained by discovering anopheles in such “empang” in Marunda Village, Cilincing, North Jakarta, which is adjacent to the Navy Special Forces Command Headquarters dormitory. This is very potential for malaria to spread considering the mobility of troops who often go in and out of endemic areas both at home and abroad. Thus, it is necessary to improve coordination and cooperation between various stakeholders, especially the Province Health Department, the Navy Health Service, or other related agencies.